Do mobile pensioners threaten the deferred taxation of savings? - Volker Meier; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2011)
We investigate optimal taxation of lifetime income with and without an emigration option during old age. The government sets the rates of deferred taxation and of possibly reduced taxation of interest. If agents are immobile, the optimal policy consists in full deferral of income taxes on savings and a full taxation of interest. Mobility of the old calls for lower degrees of deferral and reduced taxation of interest. However, the optimum never entails full immediate taxation of savings in combination with full tax exemption on capital income.
Keywords: H21; H24; H26; 330; deferred taxation; income tax; savings; migration